2008
DOI: 10.1007/s11096-008-9215-6
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of drug use in the public sector primary health centers of Bhopal district

Abstract: Antibiotic use in our setting was high, while generic drug prescribing was lower in comparison to other recent studies in Asia. The study provides a baseline measure against which changes in practice can be monitored as elements of the state drug policy are put into place.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
7
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 7 publications
4
19
7
1
Order By: Relevance
“…The socio-demographic details of the study participants are represented in Table 1 and the result shows male predominance (60.52%) in antimalarial usage. The antimalarial are prescribed highly in the age group of 31-45 years (21.58%) which was like previous studies conducted in various areas 10,11 and this reflects that the prevalence of the disease was higher among adult patients in this region during the study. During the study, out of 98 subjects prescribed with antimalarial drugs, 46 subjects showed malarial infection and 52 patients were diagnosed with non-malarial infection and in 46 malarial cases, 78.78% of patients were serum positive for Plasmodium falciparum and 21.22% were with Plasmodium vivax and mixed type of infection.…”
Section: Resultssupporting
confidence: 83%
“…The socio-demographic details of the study participants are represented in Table 1 and the result shows male predominance (60.52%) in antimalarial usage. The antimalarial are prescribed highly in the age group of 31-45 years (21.58%) which was like previous studies conducted in various areas 10,11 and this reflects that the prevalence of the disease was higher among adult patients in this region during the study. During the study, out of 98 subjects prescribed with antimalarial drugs, 46 subjects showed malarial infection and 52 patients were diagnosed with non-malarial infection and in 46 malarial cases, 78.78% of patients were serum positive for Plasmodium falciparum and 21.22% were with Plasmodium vivax and mixed type of infection.…”
Section: Resultssupporting
confidence: 83%
“…The demographic details of patient attending health care facilities shows not much variation between male and female attending the health facilities in comparison to the other studies conducted in various areas 18,19 reflecting that the prevalence of disease was higher among adult patient in this region during the study period.…”
Section: Discussionmentioning
confidence: 51%
“…14,19 With regards to study conducted at other developing countries like India, Saudi Arabia, Bahrain it was comparatively high. 18,26,[28][29][30] Prescribing by generic name is recommended by WHO as it enables selection of more alternatives and also has major impact in cost minimization. The factor influencing low generic prescribing may be due to poor regulation and enforcement, drug promotion and less number of generic drug productions in Nepal.…”
Section: Discussionmentioning
confidence: 99%
“…Study conducted at Bhopal (India) [28], Iran [29] and Jordan [30] reported that antibiotic percentage of encounter was. 63.5%, 61.9 % and 60.9% which was higher as compared to our study.…”
Section: Discussionmentioning
confidence: 99%